The ramp around the world: the composition of a post-Wolrd War II project atlas - Beltramini, Luiza Paes de Barros Camara de Lucia; Castral, Paulo César (Revista Nacional de Gerenciamento de Cidades, 2020)
The article proposed here reports on reading the master's student's research object using the iconological method created by the German historian Aby Warburg - the Atlas. The research in question has as the main object the reading of works that have the ramp as an architectural notation, a concept created by the Swiss architect Bernard Tschumi. Starting from a quick elucidation on the theoretical basis of the mother research, the process of building the universe of works is explained through searches in large portals for the dissemination of architectural projects, and those that meet the requirements created by the author are selected. Following the initial clarifications, there is a clarification of the German historian's methodology when composing the method that today is known as Atlas. Even though Atlas is a great help tool, it was concluded that secondary analyzes are necessary to bring the researcher closer to objects so that categories are created and from these object-works are highlighted for a more detailed assessment. All of these analyzes are carried out to find these object-works that will be studied to understand the ramp as architectural notation in post-World War II projects.